'The chearful haunts': John Armstrong (1709–1779), physician, poet, satirist and leveller of medical knowledge. (November 2015) - Bryan, Charles S; Scott, Patrick
John Armstrong, the first honours graduate of the University of Edinburgh School of Medicine, was famous in his day for a lengthy didactic poem entitled The Art of Preserving Health (1744). He is now obscure except to scholars specializing in the 18th century and, when discussed at all, often dismissed as a failed physician who wrote mediocre poetry in a quest for money and fame. A new exegesis by Adam Budd exhumes Armstrong as an original voice who offered timely and reassuring advice to Britons as they braced for another epidemic of plague; who depicted illness through the lens of a vulnerable and sympathetic physician, and who was perhaps above all else a leveller of medical knowledge. Elaborating on Budd's thesis, it would seem that Armstrong, a complicated man, has frequently been misread and was in some ways ahead of his time.